How cryogenic techniques help in machining of nickel alloys? A review. Issue 4 (4th July 2018) - Deshpande, Yogesh Vasantrao; Andhare, Atul B.; Padole, Pramod M.
ABSTRACT: Nickel alloys are extensively used in aerospace, automotive, marine, nuclear, petro-chemical and food processing industries due to properties like high strength, resistance to heat, resistance to corrosion, etc. However, machining of these alloys pose many challenges in machining such as: work hardening, high temperatures at the cutting zone, rapid tool wear, reduced tool-life, etc. Attempts are made to overcome these challenges by using various cryogenic techniques. This paper, therefore discusses different techniques such as cryogenic cooling, cryogenic treatment of tool and simultaneous use of cryogenic cooling of tool and heating of workpiece (hybrid technique) and their effects on machinability of Nickel alloys with the help of indicators like tool-life, surface roughness, residual stresses, etc. It is concluded that cryogenic techniques are helpful in improving the machining performance by way of improvement in tool-life and surface quality. This happens due to better cooling by cryogen and improved tool properties after cryogenic treatment. However, based on the published works, it is not possible to decide about the following: correct amount of cryogen required for cooling, appropriate cryogenic tool treatment cycle to be used and the best parameters for machining of Nickel alloys. Therefore, future research should focus on these aspects.